Potensi degradasi lingkungan dampak eksistensi karbofuran di Indonesia - Alfiansyah, Harry; Ardikoesoema, Nurmansyah; Samuel, Juan (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Carbofuran is one of the active compound elements as the primary ingredient for making the world's most toxic broad-spectrum and systemic carbamate pesticides, commonly used as insecticides, nematicides, and acaricides for agricultural, household, and industrial purposes. Based on the report of the eighth meeting of the Rotterdam Conference in 2017, it was agreed that the active compound carbofuran is prohibited because of its hazardous impact on human health and the environment. Apart from being harmful to human health and the environment, it is also very deadly to mammals, birds, fish, and wildlife due to its anticholinesterase activity, which inhibits acetylcholinesterase and butyrylcholinesterase activity. Carbofuran is associated with endocrine, reproductive, cytotoxic, and genotoxic disorders in humans. Therefore, the environment contaminated with carbofuran is a significant concern and requires severe treatment that is adequate, sophisticated, and effective to be able to mitigate the degradation that occurs. This paper briefly discusses the toxicity of carbofuran and its toxicological impact on the environment esp, especially the role of the government in regulating the distribution of pesticides and mitigating the threat of impacts from pesticide use. This writing method uses a literature review technique, which the author describes to conclude. Activities to control pesticide pollution and its adverse effects on the environment and non-target organisms are carried out by (1) Issuing standardized legal regulations to prohibit the use and distribution of high-risk pesticides. So, with regulations, the adverse effects of pesticides can be reduced. However, it is necessary to pay attention to the social impacts that might occur if the government imposes a ban on the use of chemical pesticides due to the high dependence of Indonesian farmers on the use of chemical pesticides derived from carbamates, such as carbofuran. (2) Implement stricter regulations regarding the use of dangerous chemical pesticides. (3) Encourage industry to develop and produce environmentally friendly pesticides to realize sustainable agriculture. One environmentally friendly pesticide is the Biopesticide method. (4) Applying new scientific methodologies, technologies, and valid measures, such as integrated pest management (IPM). Furthermore, further research is needed focusing on environmental exposure and assessment of health risks related to carbofuran pesticides to better understand the use and management of pesticides in the future and also research related to innovations in integrated pest management (IPM).